41-Usûlî'nin Şiirlerinde Sevgili Portresi - YALÇINKAYA, YAĞIZ (Yakup YILMAZ, 2022)
Klâsik Türk şiirinin estetik geleneği içinde oluşmuş aşk üçgeninin baş öğesi olan sevgili, yüzyıllarca şairlerin dilinden düşmemiştir. Yegâne olan sevgili, bu üçlemede âşık rolüne bürünen şairin şiirlerinde klâsik nazmın estetik değerleri içinde gâh ay gâh güneş olmuş; boyu selviye saçı sümbüle benzetilmiştir. O, eziyet ve cefaları ile vefadan habersiz, erişilmez bir tip olarak tasvir edilmiştir. Çok geniş bir coğrafyada ve çok uzun bir zaman diliminde var olmuş Klâsik Türk şiiri, kendi geleneği içerisinde idealize edilmiş bir sevgili tipi kurgulamıştır. 16. yüzyılda Vardar Yenicesi’nde yaşamış Usûlî, sevgiliyi dilinden düşürmeyen Klâsik dönem Türk şairlerinden biri olmuştur. Hayatında tasavvufun belirleyici yeri olan şair Klâsik Türk şiirinin estetik anlayışını tasavvufî dü şünceleriyle harmanladığı şiirleri ile klâsik edebiyat literatürüne önemli bir divanı miras bırakmıştır. Çalışmada, Usûlî Divanı’nda şairin edebî kişiliği ve şiir anlayışı çerçevesinde sevgili tipinin nasıl bir portre çizdiği üzerinde durulacaktır.

The beloved, who is the main element of the love triangle formed within the aesthetic tradition of Classical Turkish poetry, has not fallen into the language of poets for centuries. In the poems of the poet, who assumed the role of lover in this trilogy, the lover, who is unique, within the aesthetic values of classical verse, became moon, sun; the length of cypress hair is likened to hyacinth; He is depicted as an inaccessible type, unaware of his torment and suffering and loyalty. Classic Turkish poetry, which has existed in a very wide geography and in a very long period of time, has constructed an idealized type of lover within its own tradition. Usûlî, who lived in the Vardar Yenicesi in the 16th century, became one of the Classical Turkish poets who kept talking about his beloved. The poet, who has a decisive place in Sufism in his life, left an important divan to our classical literature literature with his poems in which he blended the aesthetics of Classical Turkish poetry with mystical thoughts. In this study, In Usûlî's Divan, it will be focused on what kind of a portrait the lover type draws within the framework of the poet's literary personality and understanding of poetry.
Portrait of the Beloved in Usuli's Poems
Keywords: Usûlî; Sevgili; 16. Yüzyıl; Divan